MITOTIC AND KARYOTYPE OF INDIGOFERA SUFFRUTICOSA MILL. IN CENTRAL JAVA - Wahyu Kusumawardani; Muzzazinah Muzzazinah; Murni Ramli (Floribunda, 2021)
Wahyu Kusumawardani, Muzzazinah  & Murni Ramli. 2021. Mitotic and Karyotype of Indigofera suffruticosa Mill. in Central Java. Floribunda 6(6):  213–219 . — Indigofera suffruticosa has been widely used by Indonesians, but its cytological information is still limited. This study was aimed to observe the mitotic phases and chromosome structures of I. suffruticosa. The analysis was performed on I. suffruticosa sampled from Magelang, Central Java. Mitotic phases and chromosomes’ structures were observed using root tips prepared with the squash method. The chromosome morphological structure was analyzed with karyotype maps using Image Raster, Corel Draw, and Microsoft Excel. The observation showed that I. suffruticosa were at various mitosis phases starting from prophase, pro-metaphase, metaphase, anaphase, and telophase. The chromosome in the pro-metaphase was analyzed for its karyotype morphology. The species has some diploid chromosomes (2n = 16). I. suffruticosa’s chromosomes have an average chromosome’ length of 2.08 µm with submetacentric and metacentric types. Data about the chromosome structure of I. suffruticosa from Indonesia could complement the novelty of the taxonomic classification information obtained by previous researchers.